Trends of College Faculty Towards Psycho-lab (Journal of the College of Education for Women, 2019)
1. Building an analysis tool that determines the strength of a relationship in a psychological experiment. 2. To identify the degree of direction of the research sample on the lab psychological variable according to gender (males - females). 3. Recognize that there are no statistically significant differences about the psychological laboratory variable according to gender (males - females). To investigate the goals of the current research, seek to develop a tool to measure attitudes towards laboratory psychological variables that are scaled according to a range of 24 items including paragraphs ranging from positive to negative attitudes that gradually change from significantly agree, moderately agree, slightly agree, not agree, and I do not agree at all.The sample was chosen from 120 students from the teaching research community at the University of Baghdad (males - females) colleges (Education for Girls, Ibn Rushd of Education, Arts, Ibn al-Haytham) for the academic year 2013-2014. We have discovered the following findings in relation to the research procedures that we applied and these are as follows: 1. The degree of desire and willingness is influential in the positive direction of the relationship with teaching in a laboratory psychological experiment. 2. No statistically significant differences in the samples in the psychological experiment in accordance with the variable gender (male - female). Researchers recommend the following: 1. Guidance for the students to take advantage of existing hardware in the laboratory for the application of psychological research and studies. 2. Attention the University of Baghdad on the section of applied laboratory for Department of Psychological Sciences related to the topics of psychology. The researchers propose the following: 1. Measuring the level of the trend towards the measured psychological variable in the laboratory at the Baghdad University within students in the faculties of science and education who are also studying psychology. 2. Conduct a study on the use of laboratory psychological problems.